The tourism workforce and policy: Exploring the assumptions using Crete as the case study - Vaughan, David Roger; Andriotis, Konstantinos (My University, 2004)
The size of the tourism workforce has grown rapidly to the extent that today, travel and tourism is considered to be the world's largest employer. The potential of tourism for generating jobs in areas where there are few other alternatives for employment has resulted in many governments electing to expand their tourism industry. Nevertheless, tourism has been criticised for creating part-time, seasonal, low quality and informal jobs often occupied by migrants and females. This paper sets out the main characteristics of the tourism workforce as reported by academic papers, identifies whether the same characteristics are evident on the island of Crete (Greece), and discusses the issues surrounding tourism policy formulation in relation to the tourism workforce of Crete. The conclusion is that very often jobs in tourism are judged, and responses formulated, on a normative (value laden) basis (an ideal) without full consideration being given to the actual (technical) underpinnings and implications.
Keywords: Crete; Jobs; Policy; Quality; Seasonality; Tourism